Analisis Rencana Bisnis di Startup Kecantikan Abadi Ecoxyn - Nurlatipah Perawati, Gina; Umbara, Taufan (eProceedings of Management, 2024)
Ecoxyn as a new brand wants to invite Gen Z to be aware and call for protecting the environment in order to takeadvantage of opportunities and effective strategies to develop the Ecoxyn business. Ecoxyn wants to continue todevelop its business so that it can be sustainable at a time when many competitors are present, therefore Ecoxyncontinues to carry out its business strategies and plans, one of which is this research, namely to analyze effective andefficient business plans and strategies for Ecoxyn's business processes. The method used to analyze Ecoxyn's businessplan is an objective and qualitative method, because it is a report on a business that is managed by itself. Aftercarrying out this analysis, it can be seen that Ecoxyn is able to compete with other local brands. This is based on theanalysis carried out in this research in the form of PESTEL analysis, 4P's Marketing Mix, Business Model Canvas,Porter's 5 Forces, Competitive, SWOT & TOWS, STP, as well as analysis of Ecoxyn's marketing, operational,management and financial plans and strategies, the results obtained that Ecoxyn has been able to compete withcompetitors' positions in terms of price and quality and is in a period of improvement in terms of online and offlinemarketing. Therefore, Ecoxyn gets a profit of IDR 57,200,000 during September 2023 - 2024 with initial fundingrequired of IDR 15,600,000.Keywords-PESTEL analysis, 4P's marketing mix, business model Canvas, Porter's 5 Forces, competitive, SWOT &TOWS, STP, marketing, operational, management and financial plans and strategy